Language Labs: Their Impact on English Language Learners - Long, Jeanette R (ProQuest LLC, 2013)
Unacceptable use of the English language by English language learners (ELLs) at the college level has been determined to be a major deterrent to their success in academia. The problem is that ELLs who complete a language acquisition program may not necessarily perform well in core academic subjects because of persisting language barriers. It is not known to what extent longer use of the language lab in English for Academic Purposes (EAP) courses affect the academic success of these students. In addition, it is not known to what extent tutoring opportunities, additional drills and exercises not required by the course, extended opportunities to practice oral language, the learners' previous educational level, and the learners' first language effectiveness affect the students' language learning process. The purpose of this quantitative study is to determine to what extent time spent practicing in the language lab of a college setting affects the academic success of learners in a higher education institution. The other purpose of this study is to research the effect that other variables may have on effective language learning; specifically, whether tutoring opportunities, additional drills and exercises not required by the course, extended opportunities to practice oral language, the learners' previous educational level, and the learners' first language effectiveness affect language learning. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]